2020
DOI: 10.1111/dth.14180
|View full text |Cite
|
Sign up to set email alerts
|

Sequential paradoxical psoriasiform reaction and sacroiliitis following adalimumab treatment of hidradenitis suppurativa, successfully treated with guselkumab

Abstract: Paradoxical reactions during treatment with a biologic agent are defined by the appearance or exacerbation of a pathological condition that usually responds to this drug while treating another condition. A 26-year-old woman presented with a 3-year history of Hurley Stage III hidradenitis suppurativa (HS) involving the groin, buttocks, and pubis, which had been refractory to topical antibiotics and corticosteroids, doxycycline, rifampicin, and clindamycin in combination. F I G U R E 1 Hurley stage III Hidradeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 9 publications
3
18
1
Order By: Relevance
“…There is only one case of PsA flare (in a patient with long‐standing PsA) that appeared to be triggered by guselkumab 5 . Conversely, a case of concomitant hidradenitis suppurativa, sacroiliitis and paradoxical psoriasiform reaction to adalimumab was successfully treated with guselkumab 7 and a case of a palmoplantar pustular reaction (in a patient with severe psoriasis treated with ixekizumab) was successfully treated with guselkumab 6 …”
Section: Figurementioning
confidence: 99%
“…There is only one case of PsA flare (in a patient with long‐standing PsA) that appeared to be triggered by guselkumab 5 . Conversely, a case of concomitant hidradenitis suppurativa, sacroiliitis and paradoxical psoriasiform reaction to adalimumab was successfully treated with guselkumab 7 and a case of a palmoplantar pustular reaction (in a patient with severe psoriasis treated with ixekizumab) was successfully treated with guselkumab 6 …”
Section: Figurementioning
confidence: 99%
“…We administered the psoriasis dosage regimen as in many previous cases: in fact, so far only four patients were treated with a higher dosage (100 mg every 4 weeks), however, without a greater advantage. 7 We observed a significant improvement in our patient at week 16, according to literature review, [3][4][5][6][7] but a long follow-up period is needed to confirm the high response rate.…”
mentioning
confidence: 54%
“…In a few previous studies, guselkumab showed good results in Hurley stage II or III HS patients, not all presenting a concomitant or induced psoriatic condition. [3][4][5] It is reported that IL-23/Th-17 pathways, over expressed in immunopathological features of psoriasis and paradoxical psoriasiform reactions, could play a crucial role in the pathogenesis of HS including IL-23, highly expressed by macrophages infiltrating affected skin. 6 Since our patient developed vulgar psoriasis during therapy with adalimumab without clinical improvement, guselkumab was elected as second-line biological therapy.…”
mentioning
confidence: 99%
“…Adalimumab, a fully human monoclonal IgG1 antibody directed toward membrane-bound TNF α is the only FDA-approved biologic therapy for moderate to severe HS [ 6 , 23 , 24 ]. The approved standard dosing regimen of adalimumab is 160 mg at baseline (week 0), and 80 mg at week 2, followed by 40 mg weekly from week 4 [ 16 , 25 , 26 , 27 , 28 ]. Some cases of paradoxical HS have been reported in patients suffering from chronic inflammatory bowel diseases treated with adalimumab who developed moderate to severe forms of paradoxical HS [ 20 , 29 ].…”
Section: Resultsmentioning
confidence: 99%